Delivering of Over-Expression Construct OsWRKY76 Candidate Gene in Rice cv. Nipponbare through Agrobacterium tumefaciens - Apriana, Aniversari; Sisharmini, Atmitri; Enggarini, Wening; Sudarsono, Sudarsono; Khumaida, Nurul; Trijatmiko, Kurniawan R. (Jurnal AgroBiogen, 2011)
Plant genetic improvement can be done through classical breeding or genetic engineering. WRKY is a transcription factor involved in regulating plant defense responses. OsWRKY76 gene is located in a narrow segment of chromosome 9 which is identified previously to be related to wide spectrum resistance in rice. A sequence of OsWRKY76 (+1.200 bp) has available in the gene bank and it makes possible to isolate, clone, and construct the gene into over-expression vector. The aim of this research was to assemble an over-expression construct of OsWRKY76 candidate gene and introduce it into rice through Agrobacterium-mediated transformation. A construct of pCAMBIA-1301::35S::OsWRKY76 has been successfully assembled and transformed into embryogenic calli of rice cv. Nipponbare using A. tumefaciens strain Agl-1 and EHA 105. A number of 126 independent lines has been produced, in which Agl-1 showed 3.8 times more efficient than EHA 105. PCR analysis of randomly selected 25 independent lines showed that all of them positively contained hptII gene, a selectable marker used in the over-expression construct of the OsWRKY76 candidate gene. Based on the result, it could be concluded that the over-expression construct of OsWRKY76 candidate gene have been successfully introduced into the tissue of Nipponbare.